Optimal chemigation duration model based on the crop and environment effects - Wang, Hui; Shi, Wenpeng; Wang, Wene; Hu, Xiaotao; Ling, Gang; Wei, Rong (International Journal of Agricultural and Biological Engineering, 2023)
Herbicides with drip irrigation (chemigation) could control the herbicides application accurately as the irrigation technology, and could reduce the harm to humans and the environment. However, the herbicide concentration is not consistent in the advancing process along the drip irrigation tape of different lengths, which not only influences the crop growth and results in herbicide residue. In this study, the crop and environmental effects of chemigation were discussed, potassium permanganate was used to replace herbicides, and a laboratory test was conducted to determine the best application duration. Based on this result, the maize field experiment of chemigation under plastic mulch was carried out to compare the effects of maize growth index, yield and herbicide residue for determining the optimal chemigation mode. The result shows that there is no significant difference in the application uniformity among treatments, but the leaf area index (LAI), yield, and double-ear rate of maize under continuous application (CA) were higher than those under periodic application (PA) and no application (NA) significantly. One month after the application, the acetochlor residue of the two modes was less than 1%, which would not cause pollution to the surrounding environment. And there was a significant linear regression relationship between the length of drip irrigation tape and the optimal application duration under the same acetochlor dosage. Keywords: chemigation, irrigation mode, maize, environment DOI: 10.25165/j.ijabe.20231604.7408 Citation: Wang H, Shi W P, Wang W E, Hu X T, Ling G, Wei R. An optimal chemigation duration model based on the crop and environment effects. Int J Agric & Biol Eng, 2023; 16(4): 41-50